Zullo, Julia (2015): Piquetes y piqueteros en la prensa Argentina (1996-2002) - Testoni, Federico E.; Zukerfeld, Gilda (Revista Latinoamericana de Estudios del Discurso, 2020)
Reseña ZULLO, Julia (2015). Piquetes y piqueteros en la prensa Argentina (1996-2002). San Fernando: La Bicicleta. 318 pp. ISBN: 978-987-45712-4-3.